A multi-ligation strategy for the synthesis of heterofunctionalized glycosylated scaffolds. Issue 25 (28th August 2014) - Thomas, Baptiste; Fiore, Michele; Daskhan, Gour Chand; Spinelli, Nicolas; Renaudet, Olivier
Abstract : Well-defined heterofunctionalized glycosylated scaffolds with unprecedented molecular combinations have been prepared using up to five different bioorthogonal ligations. Abstract : Well-defined heterofunctionalized glycosylated scaffolds with unprecedented molecular combinations have been prepared using up to five different bioorthogonal ligations. This approach opens up chemical access to a diversity of biomolecular structures with high biological potential.